TUJUH ‘C’ DALAM PROGRAM HUMAS JAKARTA SMART CITY - Ratu Almerlia Destriana Bajri; Irwansyah Irwansyah (Inter Script : Journal of Creative Communication, 2019)
This study examines and researching message delivered on the Public Relations program of Jakarta Provincial Government in order to communicate the Jakarta Smart City program. The concepts used in this study are: Seven ‘C’ (Credibility, Context, Content, Clarity, Continuity & Consistency, Channel, Capability Of The Audiens). This is an explanative research with population is as much as 25442. Sampel are 100 using simple random. Data is processed using SPSS 20.0 then presented in the form of frequency tables, mean values and KMO analysis. Results obtained examines Anti-Image Correlation > 0,5. H0 is rejected and H1 is accepted. That means, Seven ‘C’ (credibility, context, content, clarity, continuity and consistency, channel and capability of the audience) can be found in the Public Relations program of Jakarta Smart City for residents of Petukangan Utara, South Jakarta.